Penerapan Model Pembelajaran Advence Organizer Untuk Meningkatkan Kemampuan Pemahaman Matematis - Nurul Hidayati; Eka Rosdianwinata; Ika Meika (Universitas Mathla'ul Anwar Banten, 2019)
The purpose of this research is to find out the extent of increasing mathematical understanding ability between students who get the Advance Organizer learning model and students who do not get the Advance Organizer learning model. This research is a quasi experimental design type of non equivalent pretest-postest control group design. The population in this research were students of information systems at the faculty of technology and information by taking a sample of two classes, namely class A as an experimental class and class B as a control class. The research instrument used was a mathematical understanding ability test. Based on the research results, it is known that there are differences of mathematical understanding ability between students who get the Advance Organizer learning model and those who do not get the Advance Organizer learning model. So by using the Advance Organizer learning model, it can improve the ability of mathematical understanding when compared to the learning process that does not use the Advance Organizer model. In addition, the activities and understanding of students in learning reflect the implementation of learning well and students give positive responses, where the learning that is carried out can further enhance students’ motivation and mathematical understanding abilities in solving problems.